Developing an Evaluating System to Improve Efficiency, Effectiveness and Governance in the Public Sector: the Case of the Program of Subsidies to Exporting Companies in Brazil - Frederico Lustosa da Costa; José Cezar Castanhar; Daniela Gomes Castanhar Reyes; Gustavo de Oliveira Almeida (BBR: Brazilian Business Review)
Improving a country’s export is widely acknowledged as a strategic issue. For a developing country, the benefits are multiple: expand the markets for goods and services to a global scale contributing to job creation, set technological and management standards for the sectors of the economy and reduce the country’s external vulnerabilities by generating reserves. Those benefits justify the adoption of public policies to support and foster exports, but it is essential to ensure that the resources invested in these programs are being effectively used, requiring the design and implementation of evaluation systems. This article aims to present and discuss an evaluation model for PROEX, Brazilian Program for Supporting Exports. The model proposed include definition and calculation of a set of indicators that will allow the monitoring of the extent to which the program is achieving its main objectives. We believe that the evaluation model proposed will help to improve the efficiency, effectiveness and governance of the Program.